ANALISIS KESESUAIAN MATERI BUKU TEKS BAHASA INDONESIA TERHADAP CAPAIAN PEMBELAJARAN KURIKULUM MERDEKA KELAS XI SMA - Rosmawaty; Dian Anjani Simamora; Gita Sundayini Sinaga; Lidya Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze the suitability of the material in the Indonesian language textbook for class XI SMA with the learning outcomes in the Merdeka Curriculum. Textbooks as the main learning resource play an important role in supporting the learning process, so the suitability of the material with learning outcomes needs to be examined in depth. This research uses a qualitative approach with literature study methods. Data were obtained from Indonesian language textbooks for class XI, Merdeka Curriculum learning outcome documents, and various supporting literature sources. Data collection techniques were carried out through content analysis of textbooks and compared with established learning outcomes. The results showed that in general the material in the textbook is in accordance with the learning outcomes, but there are still some shortcomings, such as the limited project-based learning and the not yet optimal development of critical thinking. Therefore, further development is needed so that textbooks can support learning optimally.